2017
DOI: 10.1038/srep42039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exogenous selenium supply on photosynthesis, Na+ accumulation and antioxidative capacity of maize (Zea mays L.) under salinity stress

Abstract: The mechanism of selenium-mediated salt tolerance has not been fully clarified. This study investigated the possible role of selenium (Se) in regulating maize salt tolerance. A pot experiment was conducted to investigate the role of Se (0, 1, 5 and 25 μM Na2SeO3) in photosynthesis, antioxidative capacity and ion homeostasis in maize under salinity. The results showed that Se (1 μM) relieved the salt-induced inhibitory effects on the plant growth and development of 15-day-old maize plants. Se application (1 μM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
125
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 235 publications
(173 citation statements)
references
References 51 publications
(104 reference statements)
13
125
2
1
Order By: Relevance
“…Selenium application caused an increasing growth in rice (Oryza sativa L.) [27] and wheat (Triticum aestivum L.) [28], under both stressed and non-stressed conditions. Se has been demonstrated to regulate plant growth by strengthening the stress tolerance mechanisms such as antioxidant and secondary metabolite metabolism [29]. It has also been reported previously that Se reversed the negative impacts of soil salinity on the photochemical efficiency of photosystem II [30].…”
Section: Of 27mentioning
confidence: 84%
See 4 more Smart Citations
“…Selenium application caused an increasing growth in rice (Oryza sativa L.) [27] and wheat (Triticum aestivum L.) [28], under both stressed and non-stressed conditions. Se has been demonstrated to regulate plant growth by strengthening the stress tolerance mechanisms such as antioxidant and secondary metabolite metabolism [29]. It has also been reported previously that Se reversed the negative impacts of soil salinity on the photochemical efficiency of photosystem II [30].…”
Section: Of 27mentioning
confidence: 84%
“…Likewise, another study reported that Se application (20 µM) in the form of sodium selenite causes improvements in the growth and yield of eggplants under varying levels of soil salinity [123]. However, higher doses of selenite were found to have deleterious effects on the growth and development stages of maize under a salt stress of 100 mM NaCl [29]. Even though Se is an essential trace nutrient to humans and other animals as an antioxidant, Se toxicity might appear at higher concentrations due to the substitution of S with Se in the structure of amino acids, followed by the inaccurate folding of proteins and thus the creation of nonfunctional proteins and enzymes [102].…”
Section: Selenium-mediated Alleviation Of Salinity Stress In Plantsmentioning
confidence: 99%
See 3 more Smart Citations